Transcriptomic analyses reveal the potential antibacterial mechanism of citral against Staphylococcus aureus - Liao, Zedong; Lin, Keshan; Liao, Weijiang; Xie, Ying; Yu, Guoqing; Shao, Yan; Dai, Min; Sun, Fenghui (Frontiers in Microbiology, 2023)
Background The emergence of multi-drug resistant Staphylococcus aureus (S. aureus) has posed a challenging clinical problem for treating its infection. The development of novel or new antibacterial agents becomes one of the useful methods to solve this problem, and has received more attention over the past decade. Citral is reported to have antibacterial activity against S. aureus, but its mechanism is yet entirely clear. Methods To reveal the antibacterial mechanism of citral against S. aureus, comparative transcriptomic analysis was carried out to analyze the gene expression differences between the citral-treated and untreated groups. The changes of protein, adenosine triphosphate (ATP) and reactive oxygen species (ROS) content in S. aureus caused by citral were also examined. Results Six hundred and fifty-nine differentially expressed genes were obtained according to the comparative transcriptomic analysis, including 287 up-regulated genes and 372 down-regulated genes. The oxidoreductase activity and fatty acid degradation pathway were enriched in up-regulated genes, and ribosome and S. aureus infection pathway were enriched in down-regulated genes. Meanwhile, physiological trials revealed a decline in ATP and protein levels, but an increase in ROS content within the citral-treated group. Thus, it can be inferred that the antibacterial effects of citral against S. aureus were likely due to its ability to decrease ATP content by down-regulating ATP synthase genes (atpD and atpG), reduce protein content, induce cell membrane and cell wall damages, accumulate ROS, and down-regulate virulence factor genes to reduce pathogenicity. Conclusion These findings revealed the antibacterial mechanism of citral was likely a type of multi-target mode that affected multiple molecular processes in S. aureus, which lays the groundwork for further exploitation of citral as a therapeutic candidate against S. aureus infections.